Pengaruh Yoga Pranayama terhadap Tingkat Stres pada Pasien Diabetes Melitus Tipe II - Ni Putu Artamevia Marcelina; I Wayan Candra (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2022)
Diabetes Melitus (DM) is a metabolic disease in which the main cause is problems with insulin secretion, insulin action or both. Patients with diabetes melitus are prone to stress. Stress that occurs can trigger physical and psychological problems. The purpose of this study was to determine the effect of pranayama yoga on the stress level of type 2 diabetes melitus patients in the UPTD Public Health Center II West Denpasar. This type of research was analytic research using a pre-experimental one-group pre-post test design. Sampling was done by simple random sampling technique. The research sample amounted to 27 people. The research instrument used the Perceived Stress Scale-10. The data analysis technique used the Wilcoxon Signed Rank Test. The results of the study before being given the intervention of yoga pranayama mild stress 5 people (18.5%), moderate stress 15 people (55.6%) and severe stress 7 people (25.9%). After the pranayama yoga intervention treatment, stress levels changed, 15 people (55,6%) mild stress and 12 (44.4%). There is a significant effect p = 0.000 between yoga pranayama on stress levels in diabetes melitus patients in the work area of UPTD Puskesmas II Denpasar Barat. Pranayama yoga can reduce the stress level of diabetes melitus patients.